Aminopropyl functionalized ordered mesoporous silica as an efficient adsorbent for separation of widely used acidulant citric acid from expired juices. Issue 17 (22nd November 2019) - Bisht, Akshay; Goyal, Akshay; Sachdev, Divya; Pasricha, Renu
ABSTRACT: The massive use of synthetic citric acid (CA) has resulted in huge burden on its disposal from the expired food and pharmaceutical products. Adsorption of CA was investigated over aminopropyl functionalized ordered mesoporous silica (SBA/APTS) by varying different parameters wherein the best optimized condition showed up to 95% CA adsorption. Electron microscopy showed the presence of CA adsorbed sites over functionalized silica, further supported by thermogravimetric and volumetric analysis. Under the best optimized condition, the mechanism of adsorption was also proposed. Separation of CA over SBA/APTS from expired lime juice showed 40% removal capacity. The adsorption measurements were best fitted on Langmuir isotherm model with maximum adsorption capacity as 133.34 mg of CA per g of adsorbate (SBA/APTS).